The Use of a Dodol Mixer Machine in the Typical Gorontalo Dodol Production House in Reksonegoro Village, Gorontalo, Indonesia - Muammar Zainuddin; Melinda Ibrahim; Siti Haisah; Rosmina Hiola (Indonesian Journal of Cultural and Community Development, 2021)
The small and medium enterprises partners for typical dodol production took longer time in cooking dodol which spend approximately 8 hours by human power. The raw material is traditionally cooked by using firewood. The raw material, heat level of firewood, and the stirring speed determine the quality of dodol produced. This activity of community service aims to apply a technology of stirring machine to produce dodol in a culturally-based enterprise activity. The solution offered to the partners is designing the stirring machine by maintaining the traditional elements for a better product quality. The cantilever body is designed by using two bases permanently planted on the floor of the cooking place so that the partners may still utilize firewood. Its strong design helps a condition of expansion effect caused by the ember. The typical dodol of Gorontalo has a solid thickness texture which requires a bigger machine torque. The driver unit implements an electricity machine of 1 Hp with 1400 rpm of speed. The electricity machine is connected to a gearbox with a 1:8 ratio aimed to reduce the machine speed. The stirrer uses a stripe metal designed with an aerodynamics concept. The small and medium enterprises partners are trained to be able to use the stirring machine for an effective process of cooking. The output target of the stirring machine technology are the cooking efficiency with 4 – 5 hours of consuming time, human power efficiency, and the increase of the daily production capacity up to twice